Records of Myodopsylla wolffsohni wolffsohni (Rothschild, 1903) (Siphonaptera, Ischnopsyllidae) on Myotis nigricans Schinz, 1821 (Chiroptera, Vespertilionidae), from the State of Paraná, Southern Brazil - Arzua,Márcia (2002)
The flea, Myodopsylla wolffsohni wolffsohni (Rothschild, 1903), had been recorded for the first time in the State of Paraná in 1940, on the bat, Myotis levis (I. Geoffroy, 1824). Previously, this species of flea had only been recorded on Myotis nigricans, in the Amazonian region. This is the second record of M. w. wolffsohni on M. nigricans in Brazil, and the first in the State of Paraná. Although this flea has been found on undetermined Chiroptera in the State of Santa Catarina, the present record represents the meridional limit of geographic distribution for the infestation on M. nigricans.